Letter from a stranger : [a novel] - Bradford, Barbara Taylor, 1933- (St. Martin's Press, 2012)
When award-winning film maker Justine Nolan returns to her beautiful childhood home, she is intrigued by an envelope she finds in her absent mother's post. But the letter inside contains a shocking revelation. If genuine it will change everything she believes about her family's recent history, her mother and her adored grandmother, Gabriele.